Efektivitas Pelayanan E-Government Dalam Pembuatan Paspor Di Kantor Imigrasi Kelas I Khusus Surabaya Jawa Timur - Afifa Afifa; Radjikan Radjikan; Supri Hartono (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2024)
This research aims to analyze and describe the effectiveness of e-Government services in making passports at the Special Class I Immigration Office in Surabaya. This type of research uses a qualitative descriptive method with data collection techniques through observation and interviews. This research uses theory from the Harvard JFK School of Government in Indrajit. The research results show that the effectiveness of e-Government services in making passports at the Surabaya Special Class I Immigration Office as a whole is quite effective. However, there are several obstacles that the government can overcome by technically expanding the system capacity to accommodate more requests on a regular basis. This allows the implementation of a more efficient and transparent queue scheduling system, ensuring users get the right time to apply for their passport.